A study of knowledge, attitude and practice towards contraception among nursing staff in district Kota Bharu - Yunos, Nik Noor Azmi Mohd; Rahman, Rahiza Ab (2002)
All of the respondents were Malays.Majority of them were married with total family income of more than RM1500.00. Community nurses were the commonest nursing category involved in this study.More than half of the respondents worked for more than 10 years.Majority of the respondents had only moderate knowledge score and staff nurses bad the highest mean knowledge score.About one third of the respondents were currently practicing any method of contraception, with majority of them preferred oral contraceptive pills.However,about 15% of them were practicing traditional methods of contraception.Staff nurses were the commonest nursing staff practicing contraception and there was significant association between level of knowledge and contraceptive practice. Majority of respondents had good attitude toward modem contraceptive methods.However,about 10% of the respondents felt that traditional methods were effective for preventing pregnancy and should be encouraged.Only 20.0% of respondents were aware/ had heard of emergency contraception and majority of them were staff nurses. Among those who had heard of emergency contraception, majority of them had poor knowledge and only 17.1% of them had practiced it.